Replacing 30 % chemical fertilizer with organic fertilizer increases the fertilizer efficiency, yield and quality of cabbage in intensive open-field production - Cui,Xinwei (2022)
ABSTRACT: The combined application of chemical fertilizer and organic fertilizer is an effective way to improve soil fertility, crop yield and quality. In this study, a field experiment was conducted to evaluate the yield, quality and fertilizer use efficiency of cabbage (Brassica oleracea var. capitata L.) grown under different ratios of organic fertilizer replacing chemical fertilizer at a rate of 225 kg N ha-l in 2019 and 2020. The fertilizer treatments included N0 (non nitrogen fertilizer), CK (only compound fertilizer was applied, N:P:K=15.0 %:6.5 %:12.4 %), T1, T2 and T3 (organic fertilizer replaced 15 %, 30 % and 45 % chemical fertilizer, respectively), and T4 (total nutrient input was reduced by 10 % under T2). Results showed that T2 had the highest marketable yield and fertilizer use efficiency, as well as the best quality. The marketable yield, vitamin C content, soluble sugar content, REN (apparent uptake efficiency of fertilizer N) and AEN (agronomic N use efficiency) of T2 increased by 32.2 %, 14,9 %, 5.5 %, 97. % and 55.6 %, respectively, in contrast, the crude fibers decreased by 34.0 %, compared with CK in the two years. In addition, T4 guaranteed the yield and moderately improved the quality of cabbage, compared with CK. Therefore, we can alternatively apply fertilization according to the purpose of capturing the highest yield or properly declining fertilizer to sustain soil texture and productivity.